Polymer Brush Friction in Cylindrical Geometries - Karel J. van der Weg; Guido C. Ritsema van Eck; Sissi de Beer (Lubricants, 2019)
Polymer brushes are outstanding lubricants that can strongly reduce wear and friction between surfaces in sliding motion. In recent decades, many researchers have put great effort in obtaining a clear understanding of the origin of the lubricating performance of these brushes. In particular, molecular dynamics simulations have been a key technique in this scientific journey. They have given us a microscopic interpretation of the tribo-mechanical response of brushes and have led to the prediction of their shear-thinning behavior, which has been shown to agree with experimental observations. However, most studies so far have focused on parallel plate geometries, while the brush-covered surfaces might be highly curved in many applications. Here, we present molecular dynamics simulations that are set up to study the friction for brushes grafted on the exterior of cylinders that are moving inside larger cylinders that bear brushes on their interior. Our simulations show that the density distributions for brushes on the interior or exterior of these cylinders are qualitatively different from the density profiles of brushes on flat surfaces. In agreement with theoretical predictions, we find that brushes on the exterior of cylinders display a more gradual decay, while brushes on the interior of cylinders becomes denser compared to flat substrates. When motion is imposed, the density profiles for cylinder-grafted brushes adapt qualitatively differently to the shear motion than observed for the parallel plate geometry: the zone where brushes overlap moves away from its equilibrium position. Surprisingly, and despite all these differences, we observe that the effective viscosity is independent of the radius of the brush-grafted cylinders. The reason for this is that the viscosity is determined by the overlap between the brushes, which turns out to be insensitive to the exact density profiles. Our results provide a microscopic interpretation of the friction mechanism for polymer brushes in cylindrical geometries and will aid the design of effective lubricants for these systems.